2021
DOI: 10.2478/jtes-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation Model of Student’s Research Activities

Abstract: The study is aimed to develop the open innovation model of student’s research activities based on the adaptation of modern scientific achievements in the context of transition to sustainable development of the education system. It advances a general approach to the design of the structure and implementation of main components of hybrid intelligent system to integrating a production-frame model of knowledge and neural network algorithm for the formation of an individual learning scenario. The software implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The authors use popular science cinema as the emergence of a new relevant learning tool to stimulate cognitive processes, critical thinking and increase the level of motivation of students. The results obtained from the introduction of the created media products into the process of teaching mathematics are consistent with the educational goals recommended by previous researchers: "to strengthen various cognitive processes, to accelerate the acquisition of various types of knowledge, to raise ethical issues, to involve students' emotions in the learning process" [5]. Our results show that the proposed methodological solutions are effective in problem, heuristic, game and other productive forms of learning, helping to develop the individuality of each student, stimulate his creative abilities by engaging in creative activity, form the ability to competently perceive, interpret, analyze and assimilate complex mathematical knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…The authors use popular science cinema as the emergence of a new relevant learning tool to stimulate cognitive processes, critical thinking and increase the level of motivation of students. The results obtained from the introduction of the created media products into the process of teaching mathematics are consistent with the educational goals recommended by previous researchers: "to strengthen various cognitive processes, to accelerate the acquisition of various types of knowledge, to raise ethical issues, to involve students' emotions in the learning process" [5]. Our results show that the proposed methodological solutions are effective in problem, heuristic, game and other productive forms of learning, helping to develop the individuality of each student, stimulate his creative abilities by engaging in creative activity, form the ability to competently perceive, interpret, analyze and assimilate complex mathematical knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…The investigation steps in the open inquiry model also facilitate students to produce findings, suggestions, or solutions to overcome environmental problems (Adler et al, 2018). The development of research-based activities for students is also one way to ensure sustainable education (Dvoryatkina et al, 2021). Since there are not many studies on the subject, it is crucial to create a teaching and learning facility that focuses on creating educational modules and models for sustainable development (Yoo & Jeon, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study, four clusters of scientific potential parameters were identified, containing specific characteristics of research activity in the environment of HILS (Figure 1): personal (achievement orientation, stylistic features of thinking, logical component of cognition); activity (cognitive processes, visual and analytical-synthetic thinking, computing and design skills); communicative (empathic abilities, communicative tolerance, verbal intelligence); productive (originality, creative activity) (Dvoryatkina et al, 2021) The main sampling strategy for statistical verification of the effectiveness of the functioning of an intelligent learning system was the method of forming a simple random sample -a simple non-repetitive sample. The main focus during group creation was on uniformity and representativeness, which is crucial for statistical processing of research results.…”
Section: Methodsmentioning
confidence: 99%
“…This article highlights the issues of studying research activities as an important contribution to the development of the theory and methodology of teaching and upbringing in general and for a deeper understanding of the contribution of various disciplines, in particular mathematics, to the development of this phenomenon. A review of the scientific literature devoted to conceptual, theoretical, methodological, procedural and technological issues of the development of research activities (Kleshcheva, 2015;Savenkov, 2013), allowed to formulate a definition reflecting the essence of this phenomenon: "research activity is an active, creative process carried out in a state of uncertainty, aimed at obtaining subjectively new knowledge about the world around students through the application of the scientific method, as well as the formation of new personal structures (scientific thinking, scientific worldview, research experience)" (Dvoryatkina i dr., 2021). We consider research activity as a unique form of education, where participants in the educational process actively master theoretical and empirical methods of scientific knowledge, form research skills and interact with each other.…”
Section: Introductionmentioning
confidence: 99%